Poldark. The complete first season [videorecording (DVD)]. - Turner, Aidan, 1983-; Tomlinson, Eleanor, 1992-; Reed, Heida; Graham, Winston ([Publisher not identified], 2015)
Ross Poldark rides again in a swashbuckling new adaptation of the hit series that helped launch Masterpiece in the 1970s. Captain Poldark is a redcoat who returns to Cornwall after the American Revolution and finds that his fighting days are far from over.